Numerical Modelling of the Multiphase Flow in an Agricultural Hollow Cone Nozzle - Paweł Karpiński; Zbigniew Czyż; Stanisław Parafiniuk (Applied Sciences)
In the field of agriculture, various types of pesticides are used to control crop pests. These chemical agents are applied using nozzles with different geometries. Regardless of their configuration and operational liquid parameters, the applied liquid jet encounters issues with wind drift and penetration efficiency. Therefore, it is necessary to optimize the spraying process. In this study, 3D numerical calculations were performed using computational fluid dynamics (CFD). A two-phase flow model based on the volume of fluid (VOF) method was used to simulate the mixing of water and air. The k-ω SST turbulence model was adopted to capture vortex phenomena. A hollow cone nozzle geometry, commonly used in orchards, was selected. Simulations allowed the analysis of pressure, velocity, and turbulence kinetic energy (TKE) in selected cross-sections. Results show that the maximum velocity of the liquid jet at the nozzle outlet exceeded 23 m/s, with the highest TKE reaching 35 m2/s2 in the vortex chamber. The computed spray cone angle was approximately 88°, while the experimental value was 80°, and the simulated mass flow rate differed by 16.7% from the measured reference. The critical flow region was identified between the vortex insert and the ceramic stem, where the highest gradients of pressure and velocity were observed.